2019
DOI: 10.1038/s41598-019-42069-1
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of second-line systemic chemotherapy for advanced biliary tract cancer: A propensity score analysis

Abstract: Whether 2 nd -line-chemotherapy (2LCTX) + best-supportive-care (BSC) benefits patients with advanced biliary tract cancer (aBTC) more than BSC alone is unclear. We therefore conducted a propensity-score-based comparative effectiveness analysis of overall survival (OS) outcomes in 80 patients with metastatic, recurrent, or inoperable aBTC, of whom 38 (48%) were treated with BSC + 2LCTX and 42 (52%) with BSC alone. After a median follow-up of 14.8 months and 49 deaths, the crude 6-, 12-, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 38 publications
3
23
0
Order By: Relevance
“…Approximately 15–25% of patients are fit enough to receive second-line therapy [ 13 , 14 , 15 ]. Several retrospective studies [ 13 , 14 , 15 ] and a randomized phase III study (ABC-06) [ 16 ] have suggested a benefit of second-line chemotherapy following progression on cisplatin and gemcitabine.…”
Section: Advanced Btc: Current Standard Of Carementioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 15–25% of patients are fit enough to receive second-line therapy [ 13 , 14 , 15 ]. Several retrospective studies [ 13 , 14 , 15 ] and a randomized phase III study (ABC-06) [ 16 ] have suggested a benefit of second-line chemotherapy following progression on cisplatin and gemcitabine.…”
Section: Advanced Btc: Current Standard Of Carementioning
confidence: 99%
“…Approximately 15–25% of patients are fit enough to receive second-line therapy [ 13 , 14 , 15 ]. Several retrospective studies [ 13 , 14 , 15 ] and a randomized phase III study (ABC-06) [ 16 ] have suggested a benefit of second-line chemotherapy following progression on cisplatin and gemcitabine. The standard second-line therapies include FOLFOX (5-FU, leucovorin, and oxaliplatin) [ 16 ], capecitabine plus irinotecan (XELIRI) [ 17 ], irinotecan monotherapy [ 17 ], and fluoropyrimidine (with 5-FU) monotherapy [ 13 ].…”
Section: Advanced Btc: Current Standard Of Carementioning
confidence: 99%
“…The common treatment for advanced BTC includes palliative treatment, radiation therapy and chemotherapeutic treatment using a combination regimen of cisplatin and gemcitabine, resulting in a median survival of only about one year [12][13][14]. Second line therapeutic options are not standardized and only show weak or moderate improvement in survival rates [15]. The lack of efficient therapeutic options and the high mortality rates demand for a better understanding of the underlying molecular mechanisms of BTC development and progression [16].…”
Section: Biliary Tract Cancermentioning
confidence: 99%
“…Benefit with second-line chemotherapy following progression on cisplatin plus gemcitabine has been suggested in a number of retrospective studies [2,[9][10][11][12] [10]. The recently reported phase III, multicenter study ABC-06 [13] randomized patients with locally advanced and metastatic BTC following progression on cisplatin and gemcitabine to active symptom control (ASC) alone or ASC plus modified FOLFOX (mFOLFOX).…”
Section: Drug Informationmentioning
confidence: 99%
“…A number of retrospective studies have suggested a benefit from systemic chemotherapy following progression on first-line chemotherapy [2,[9][10][11][12]. A randomized, phase III study (ABC-06) reported improvement of median OS in patients who were refractory to first-line cisplatin and gemcitabine and treated with modified FOLFOX plus best supportive care over best supportive care alone [13].…”
mentioning
confidence: 99%